Factors Affecting SOEs Returns in IDX - Ghazali Syamni; Wirdha Ramadhani; Wahyuddin; Faisal; Rasyidin M. (Jurnal Manajemen dan Keuangan, 2022)
This study aims to examine the effect of corporate social responsibility programs, fundamental and macroeconomic variables on returns in SOEs on the IDX. This study uses financial report documentation data obtained from the pages of the Financial Services Authority, Bank Indonesia, and the Central Statistics Agency for the period 2018-2021 so that the number of observations is 80. The data analysis method uses a static panel regression approach. The results of the study found that the stock returns of SOEs were only determined by the price earning ratio. While there are no other variables that affect stock returns, including the implementation of corporate social responsibility programs that have been carried out by state owned companies. Furthermore, this study finds that the return on assets of state owned companies is determined by inflation, current ratio, leverage and earnings per share. While the variables of corporate social responsibility, price earning ratio, gross domestic product and exchange rate have no effect on return on assets. Meanwhile, other findings of this study found that corporate social responsibility has a negative effect on return on assets, while in addition to earnings per share, exchange rates and inflation. While the other variables used do not affect the return on equity.